Preserving Identity, Embracing Change: The Survival of Pekalongan Peranakan Batik - Purnomo, Setianingsih; Annita, Annita; Depita, Natalia (ULTIMART Jurnal Komunikasi Visual, 2025)
Indonesia is famous for its cultural heritage. One of the acknowledged heritages is Pekalongan Peranakan batik, a delicate and beautiful craftmanship influenced by Asia, Arab, and Europe. The Peranakan batik combines Javanese batik-making artistry with the Chinese design planning and trading strategies. This article investigates the survival of Pekalongan Peranakan batik as an endangered culture and how the artisan batik adapts with the modern era.  The method used in this study is literature review, interview with the owner of the last producer of Pekalongan Peranakan batik and descriptive–qualitative analysis. The findings reveal that although UNESCO’s recognition of batik as intangible heritage, and Peranakan batik holds centuries-old heritage of cross-cultural exchange, this art form now risks extinction. This paper examines its historical development and contemporary challenges, arguing that revitalization through innovation is essential for its survival. Besides that, this research contributes to archiving the process and the portrait of artisan batik Liem Ping Wie in Kedungwuni, Pekalongan.   Keywords: Chinese Javanese Peranakan Batik; cultural heritage; revitalization.